2012
DOI: 10.4103/0973-6131.91702
|View full text |Cite
|
Sign up to set email alerts
|

Role of sudarshan kriya and pranayam on lipid profile and blood cell parameters during exam stress: A randomized controlled trial

Abstract: Background:Yoga is a science practiced in India over thousands of years. It produces constituent physiological changes and has sound scientific basis.Aim:Since exam stress modifies lipid profile and hematological parameters, we conducted an investigation on the effect of sudarshan kriya (SK and P) program on these parameters.Materials and Methods:Blood samples of 43 engineering students were collected at four intervals namely baseline (BL), exam stress (ES), three and six weeks practice of SK and P during exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
(33 reference statements)
2
33
0
Order By: Relevance
“… 52 A randomized controlled trial using this set of practices also reported that the controlled breathing techniques were also shown to reduce examination stress and improve blood lipid profiles in stressed college students compared with controls. 53 Interestingly, a Qigong intervention incorporating a similar bandha , or abdominal retraction technique, reported increased mood, comfort, and sociability following the practice. 54 Studies also indicate that Isha Yoga and Iyengar yoga practices restore balance to autonomic nervous system function by modulating vagal afferents.…”
Section: Discussionmentioning
confidence: 99%
“… 52 A randomized controlled trial using this set of practices also reported that the controlled breathing techniques were also shown to reduce examination stress and improve blood lipid profiles in stressed college students compared with controls. 53 Interestingly, a Qigong intervention incorporating a similar bandha , or abdominal retraction technique, reported increased mood, comfort, and sociability following the practice. 54 Studies also indicate that Isha Yoga and Iyengar yoga practices restore balance to autonomic nervous system function by modulating vagal afferents.…”
Section: Discussionmentioning
confidence: 99%
“…23 MCV has also been associated with gray matter decline 50 and ventricular enlargement. 55 One possibility is that the increased erythrocyte volume, which is found in alcohol dependence 19 and during times of stress, 56,57 may lead to erythrocytes having difficulty passing through narrow brain capillaries and subsequently affecting cognitive performance. 54 …”
Section: Discussionmentioning
confidence: 99%
“…One randomized controlled trial has demonstrated and attenuated levels of subjective stress and several hematological markers, including lymphocytes and platelet count, during exam periods following SKY training. [ 18 ] These findings have not yet been replicated, and the extent to which the effects of YES+ generalize to other health-related changes such as cardiovascular function remain unclear.…”
Section: Introductionmentioning
confidence: 99%